1999
DOI: 10.1097/00000539-199902000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Size of a Double-Lumen Endobronchial Tube Using Computed Tomographic Scan Measurements of the Left Main Bronchus Diameter

Abstract: We used computer tomographic scans to measure the diameter of the left mainstem bronchus, then selected the size of the left-sided double-lumen endobronchial tube (DLT) accordingly. We found that we could predict the sizes of the DLT fairly accurately, especially the smaller DLTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 10 publications
1
33
1
Order By: Relevance
“…In fact, this strictly resembles Porwolik’s findings [19] in slowing growth dynamics of the two main bronchi. In this study, the statistical analysis showed that the left main bronchus was nearly three times longer than the right one, in keeping with other authors [2, 4, 12, 15, 16, 18–20, 25]. Furthermore, the present study has confirmed that with relation to each other, the main bronchi evolve proportionately in length.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In fact, this strictly resembles Porwolik’s findings [19] in slowing growth dynamics of the two main bronchi. In this study, the statistical analysis showed that the left main bronchus was nearly three times longer than the right one, in keeping with other authors [2, 4, 12, 15, 16, 18–20, 25]. Furthermore, the present study has confirmed that with relation to each other, the main bronchi evolve proportionately in length.…”
Section: Discussionsupporting
confidence: 92%
“…This necessitates an extensive knowledge of fetal airway biometric parameters for particular gestational weeks to further determine pathological criteria adapted to fetal and neonatal tracheobronchial anatomy [19, 24]. Furthermore, the appropriate size of a double-lumen tube for one-lung anesthesia depends on the internal diameter of the mainstem bronchus, in which the bronchial segment of the tube is to be inserted [2, 4, 7, 8, 10, 11]. …”
Section: Introductionmentioning
confidence: 99%
“…Another report showed that tracheas were successfully intubated in 18 Asian women after selecting left DLT sizes based on CT scans. [6] Smaller sizes were required in 2% (6/300) of American adult patients because of the greater difficulty of insertion into the left mainstem bronchus than in the glottis. [7] In the current study, difficulty in passage through smaller cricoid cartilages occurred in seven patients (2.5%, 7/280).…”
Section: Discussionmentioning
confidence: 99%
“…[7] In 8 of 32 short Asian women (height, <152 cm), a left DLT <32-Fr in size (8.7 mm outer diameter of the bronchial lumen, Broncho-Cath™; Mallinckrodt, St. Louis, MO, USA) was needed. [6] Moreover, left DLTs <35-Fr (9.6 mm, Broncho-Cath™) in size were needed in 27 of 48 women with heights of 152–160 cm. [8] According to Miller's Anaesthesia, a reputed textbook, the bronchial diameter should be examined and a 32-Fr DLT should be considered for short-statured female patients (<152 cm); the DLT should be able to pass the glottis without resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation